From "Take the Square" to "Squatting" in Extremadura: Politicization of Space in the "Indignados" Movements - Allen-Perkins, Diego; Frías Campomanes, Irene (Política y Sociedad, 2018)
The 15M movement or indignados stands out among the social movements that have emphasized the citizen participation through the appropriation of space. Occupation practices present a ‘political space’ in which the conflict becomes a key analytical issue, and simultaneously, this implies a scenario of possibility for the emergence of new forms of political participation. This ethnography analyzes the social production of space in the indignados movements, through the study of the repertoires of action and identifications of the activists in three occupation processes in the autonomous community of Extremadura (Spain) between the years 2011 and 2014. The work discusses the scope and limitations of the strategies of the movements in the extension of the demands and forms of organization to institutional and representative frameworks of political participation, from the analysis of the practices of meaning and of management of the conflict that the participants develop in the spaces.
Keywords: Indignados; 15M; public space; production of space; social movements; Spain